2011
DOI: 10.1177/1077559511428801
|View full text |Cite
|
Sign up to set email alerts
|

The Availability of Neighborhood Early Care and Education Resources and the Maltreatment of Young Children

Abstract: Using Census and administrative data for 2052 Census tracts in a large urban county, this study explores the relationship between several indicators of social organization and neighborhood rates of child maltreatment for 0- to 5-year-olds. Spatial regression models demonstrate that neighborhoods with a higher percentage of 3- and 4-year-olds attending preschool or nursery school, both locally and in adjacent neighborhoods, had lower rates of early maltreatment referrals and substantiations. Neighborhoods with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 45 publications
1
61
1
1
Order By: Relevance
“…These researchers suggest that disorganized neighborhoods put parents at additional risk for maltreatment because of the multiple stressors they provide, the lack of shared social norms among residents regarding child rearing, and an absence of supportive services for parents (Ben-Arieh, 2010; Coulton, Korbin, & Su, 1999; Ernst, 2001; Freisthler, 2004; Freisthler, Bruce, et al, 2007; Freisthler, Gruenewald, Remer, Lery, & Needell, 2007; Freisthler, Gruenewald, Ring, & LaScala, 2008; Garbarino & Kostelny, 1992; Klein, 2011; Korbin, Coulton, Chard, Platt-Houston, & Su, 1998). This literature has found important associations between child maltreatment and certain neighborhood-level risk factors, most notably concentrated socioeconomic disadvantage, residential instability, racial/ethnic heterogeneity, and “child care burden” or the lack of informal resources for child supervision (Coulton et al, 2007; Freisthler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These researchers suggest that disorganized neighborhoods put parents at additional risk for maltreatment because of the multiple stressors they provide, the lack of shared social norms among residents regarding child rearing, and an absence of supportive services for parents (Ben-Arieh, 2010; Coulton, Korbin, & Su, 1999; Ernst, 2001; Freisthler, 2004; Freisthler, Bruce, et al, 2007; Freisthler, Gruenewald, Remer, Lery, & Needell, 2007; Freisthler, Gruenewald, Ring, & LaScala, 2008; Garbarino & Kostelny, 1992; Klein, 2011; Korbin, Coulton, Chard, Platt-Houston, & Su, 1998). This literature has found important associations between child maltreatment and certain neighborhood-level risk factors, most notably concentrated socioeconomic disadvantage, residential instability, racial/ethnic heterogeneity, and “child care burden” or the lack of informal resources for child supervision (Coulton et al, 2007; Freisthler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, in congruence with the theory put forth by Sampson and Groves (1989) that participation in local organizations contributes to neighborhood organization and positive outcomes for residents, Kim and Maguire-Jack (2013) found that participation in community organizations like Parent Teacher Associations was associated with lower levels of verbal abuse of children. Additionally, an emerging literature suggests that the accessibility of certain types of services may help prevent child abuse and neglect (Coulton, Korbin & Su, 1999; Dorsch, Bathman, Foster et al, 2010; Freisthler, 2013; Klein, 2011; Maguire-Jack, 2014b; Morton, 2013; Spearly & Lauderdale, 1983). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meloy and Phillips (2012) found that children whose foster parents used child care subsidies experienced fewer placement disruptions than those who caregivers did not. With respect to safety, at the neighborhood level, the local availability of ECE and rates of preschool utilization have been linked to lower rates of child welfare system involvement (Klein, 2011). Additionally, participation in Head Start, Early Head Start (EHS), and the Chicago Child-Parent Centers preschool program have all been associated with lower rates of child maltreatment, particularly over the long term (Green et al, 2014;Reynolds & Robertson, 2003;Zhai, Waldfogel, & Brooks-Gunn, 2013).…”
Section: Benefits Of Quality Early Care and Education For Children Inmentioning
confidence: 98%
“…County, California, study of early care and education resources and child maltreatment in children 0 to 5 years of age (Klein, 2011). Spatial regression models showed lower rates of child maltreatment referrals and substantiations in neighborhoods with a higher percentage of 3 to 4 year olds in preschool or nursery school and lower rates of child maltreatment referrals in neighborhoods with higher availability of licensed child care.…”
Section: Census Tracts Were Used To Represent Neighborhoods In a Los mentioning
confidence: 99%